Analisis Pendapat A. Hassan tentang Hukum Pengambilan Upah Mengajar Al-Qur’an - Trisya Aprianti; Panji Adam Agus Putra; Ira Siti Rohmah Maulida (UNISBA Press, 2022)
Abstract. Ijarah contract for religious services regarding wages for teaching the Qur'an there are differences opinion among scholars. The purpose of this study is first, to find out the implementation of wage fixing in Madrasah Riyadus Shalihin. Second, to find out the views of A. Hassan and his legal istinbath method on the law of taking the wages of teaching the Qur'an. and third, to find out the relevance of A. Hassan's opinion on the implementation of the wages for teaching the Qur'an at Madrasah Riyadus Shalihih. Qualitative research methods, with a normative juridical research approach. The data sources used are primary and secondary data sources with data collection techniques in the form of literature studies, interviews, and documentation. The data analysis technique is descriptive qualitative. The results of the study found that Madrasah Riyadus Shalihin set a salary for teaching the Qur'an Rp.25,000/month, A. Hassan have a certain view that it was permissible to take the wages of teaching the Qur'an this is based on his argument in determining the law to take the wages of teaching the Qur'an which comes from the Qur'an, hadith, and his own ijtihad, the practice at Madrasah Riyadus Salihin is more relevant to the opinion of A. Hassan with the consideration that Nowadays, it is clear that if there is no wage/ujrah, the possibility of knowledge of the Qur'an, other religious sciences or other religious services will disappear because there will be no more teachers willing to teach. Abstrak. Akad ijarah jasa keagamaan mengenai upah mengajar Al-Qur’an terdapat perbedaan pendapat di kalangan para ulama. Tujuan penelitian ini adalah pertama, untuk mengetahui pelaksanaan penetapan upah di Madrasah Riyadus Shalihin, kedua, untuk mengetahui pandangan A. Hassan serta metode istinbath hukumnya terhadap hukum pengambilan upah mengajar Al-Qur’an. Dan ketiga untuk mengetahui relevansi pendapat A. Hassan terhadap pelaksanaan upah mengajar Al-Qur’an di Madrasah Riyadus Shalihih. Metode Penelitian kualitatif, dengan pendekatan penelitian yuridis normatif. Sumber data yang digunakan sumber data primer dan sekunder. Teknik pengumpulan data berupa studi pustaka, wawancara, dan dokumentasi. Teknik analisis data yaitu analisis deskriptif kualitatif dengan pola berfikir deduktif. Hasil penelitian ditemukan bahwa Madrasah Riyadus Shalihin menetapkan upah mengajar Al-Qur’an Rp.25.000/bulan, A. Hassan berpandangan akan bolehnya mengambil upah mengajar Al-Qur’an hal ini didasarkan pada argumentasi beliau dalam menentukan hukum mengambil upah mengajar Al-Qur’an yaitu berasal dari Al-Qur’an, hadis, dan ijtihad beliau sendiri, praktik yang ada di Madrasah Riyadus Shalihin lebih relevan dengan pendapat A. Hassan dengan pertimbangan bahwa zaman sekarang sudah jelas jika tidak adanya upah/ujrah kemungkinan ilmu Al-Qur’an, ilmu-ilmu agama lain atau jasa-jasa keagamaan lainnya akan sirna karena tidak akan ada lagi guru-guru yang mau mengajar.